Adaptive Intelligent Platforms for Personalizing Cognitive Load in Inclusive Chess Environments - Shymanskyi, Oleksandr (Педагогічна Академія: наукові записки, 2026)
The contemporary development of digital technologies and the expansion of inclusive education necessitate the creation of intelligent educational environments capable of adapting the learning process to the individual cognitive capacities of learners. The use of game-based and intellectual practices, in particular chess, is highly relevant, as it promotes the development of logical thinking, concentration, and analytical abilities. In the context of inclusive education, the regulation of cognitive load is essential, since its mismatch may reduce the effectiveness of knowledge acquisition and learning motivation. The aim of the study is to substantiate the potential of adaptive intelligent platforms for the personalization of cognitive load in inclusive chess-based educational environments and to determine their capacity to enhance learning effectiveness. Methods. The study employs analysis and synthesis of scientific literature on inclusive education, digital educational technologies, and cognitive load theory. Systemic and comparative approaches are used to identify the specific features of digital tools applied in chess education. Theoretical modeling enables the identification of the potential of adaptive algorithms for personalizing learning tasks in accordance with the individual cognitive characteristics of users. Results. It is established that the application of adaptive intelligent platforms in chess-based educational environments provides flexible regulation of task complexity, learning pace, and the volume of instructional content. This contributes to the optimization of cognitive load and increases the effectiveness of learning activities. The integration of artificial intelligence elements, learning analytics systems, and personalized recommendations enables the formation of individual educational trajectories that take into account learners’ levels of preparation and educational needs. The use of chess tasks in combination with adaptive digital tools supports the development of logical thinking, strategic planning, and decision-making skills. Conclusions. Adaptive intelligent platforms demonstrate significant potential for the personalization of cognitive load in the process of learning chess within an inclusive educational environment. Their application enhances the effectiveness of the educational process, supports the formation of individual learning trajectories, and fosters the development of cognitive and analytical abilities among learners. Further research should focus on the development of models for integrating adaptive artificial intelligence algorithms into digital educational platforms.